2011
DOI: 10.1002/jbmr.497
|View full text |Cite
|
Sign up to set email alerts
|

Biological constraints that limit compensation of a common skeletal trait variant lead to inequivalence of tibial function among healthy young adults

Abstract: Having a better understanding of how complex systems like bone compensate for the natural variation in bone width to establish mechanical function will benefit efforts to identify traits contributing to fracture risk. Using a collection of pQCT images of the tibial diaphysis from 696 young adult women and men, we tested the hypothesis that bone cells cannot surmount the nonlinear relationship between bone width and whole bone stiffness to establish functional equivalence across a healthy population. Intrinsic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
110
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(142 citation statements)
references
References 57 publications
29
110
2
Order By: Relevance
“…Prior work showed that women build more slender bones with less cortical area compared with men, even after adjusting for body size [7,18]. Our prior research has shown that slender bones have a lower cortical area compared with wider, more robust bones [13]. It was unclear whether the lower cortical area reported in the long bones of women was consistent with them having a more slender structure.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Prior work showed that women build more slender bones with less cortical area compared with men, even after adjusting for body size [7,18]. Our prior research has shown that slender bones have a lower cortical area compared with wider, more robust bones [13]. It was unclear whether the lower cortical area reported in the long bones of women was consistent with them having a more slender structure.…”
Section: Discussionmentioning
confidence: 89%
“…Robustness, which is a standard term used to describe the amount of transverse expansion relative to longitudinal growth [19,24], was calculated as total area/length. Cortical tissue mineral density, which is proportional to tissue modulus [13], was calculated from the mean gray value using the calibration standard. A bone strength index was calculated as cortical tissue mineral density 9 rectangular moment of inertia about the mediolateral axis (I ML ), which correlates with the bending stiffness and strength measured for cadaveric long bones loaded to failure in four-point bending [26].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations